(untitled) (Bulletin KNOB, 1991)
Since the 1930’s the beautiful historical town centre of Willemstad in Curaçao falls into decay. Not before 1980 the town could depend on governmental intervention and support, which growing attention still was strengthened by the Unesco World Decade for Cultural Development, the Dutch Unesco-committee nominating the Willemstad-restoration a specific project. In 1989 an ambitious Plan of Monuments was presented. At the moment four organizations are set up to coordinate the total process of restoration. Will this plan really appear to be the magic wand to change degenerated Willemstad into a vital town with a truce of monuments showing to full advantage again? In this article some aspects of the plan are discussed with two experts. Percy Henriquez (Curaçao 1909) was trained an engineer and occupied different posts on the island of Curaçao from 1948 till 1963. Henriquez advocated a wider substructure of the protection of monuments as part of a total plan to economical revitalization comprising area planning, town renovation and tourism. He reproaches post-war Holland an anti-colonialist mood and an ordinary lack of sense of responsibility with respect to the ex-colonies. The Curaçao Plan of Monuments is a monstrum of complexity after Dutch organizational structures. The plan misses the indication of specific museum areas in Willemstad as well, although Henriquez pleaded the far-reaching restoration of certain quarters as direct attractions for tourists. The development of the Brion Square illustrates Henriquez’ fear that the Plan of Monuments does not fit into Curaçao relations. The Brion Square is a largely unbuilt strip on the western bank of the Annabay which separates both central parts of Willemstad, Punda en Otrabanda. While the Curaçao Plan of Monuments only just had been presented the Curaçao authorities gave a refusal for a redestination-project of the Brion Square to the French investment-group Ultra Classic, the sketches of this group showing a new, far-reaching building up with a height of more than six layers. Ben Smit (Amsterdam 1922) was trained an architect and settled on Curaçao in 1943. During the fifties Smit was chairman of the Committee of Architecture of the Cultural Centre of Curaçao and restored the historical houses Stroomzigt and Penha. Smit focuses the redestination of the Brion Square around the square. The buildings must harmonize with the other bank, which in fact is the eastern wall of the square. A new western front destroys the square’s openness and the pleasant changing perspectives of the alleys coming out on it. According to Smit architects and contractors in Curaçao lack restoration-expertise because of their insufficient knowledge of old local building methods and materials. Adaptations and additions to monuments must be carried out as unobtrusively as possible, but the imitation of historical styles to stress tourism rather than the liveableness of the built environment tends to an architectural fair. Therefore Smit is opposed to the institution of a museum area in Otrabanda. Apart from the Plan of Monuments to promote the Willemstad-restoration, modern Antillean architecture must be evaluated at the same time. To provide the historically built environment with good modern architecture is almost as important as her preservation.